2016
DOI: 10.1007/s12593-015-0194-2
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Screw Fixation of Scaphoid Waist Fracture Non-Union Without Bone Grafting

Abstract: The aim of the study was to evaluate results of volar percutaneous headless compression screw fixation without bone grafting in 21 patients with scaphoid waist nonunion fractures. The inclusion criteria in this series were scaphoid waist fracture nonunion with intact cartilaginous envelope, minimal fracture line at nonunion interface, no cyst or sclerosis, no avascular necrosis and normal scapholunate angle without humpback deformity. There were 17 male and 4 female patients with an average age of 23 years (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 10 publications
2
17
0
4
Order By: Relevance
“…More recent studies have continued to demonstrate union rates of 85.7% to 100% with 91.7% to 100% of patients returning to previous work or activity levels. 2,3,5,12,16 Somerson et al 3 had the lowest union rate (85.7%), but that cohort had a mean delay of treatment of 13.6 months from injury compared with less than a year for most others. 1,5,6,12,16 In addition, most of the nonunions involved the proximal pole.…”
Section: Rationale For Screw Fixation Alonementioning
confidence: 98%
See 4 more Smart Citations
“…More recent studies have continued to demonstrate union rates of 85.7% to 100% with 91.7% to 100% of patients returning to previous work or activity levels. 2,3,5,12,16 Somerson et al 3 had the lowest union rate (85.7%), but that cohort had a mean delay of treatment of 13.6 months from injury compared with less than a year for most others. 1,5,6,12,16 In addition, most of the nonunions involved the proximal pole.…”
Section: Rationale For Screw Fixation Alonementioning
confidence: 98%
“…Several techniques require a second incision, 1,7,8,15,25 and formal grafting often requires an open approach with disruption of the capsule and ligaments and potential danger to the dorsal radial artery. 12,13,16 Garcia-Elias et al 30 found that an open volar approach resulted in increased scapholunate and lunocapitate angles, facilitating carpal collapse. Conversely, a recent meta-analysis found no difference in outcomes between approaches.…”
Section: Rationale For Treatmentmentioning
confidence: 99%
See 3 more Smart Citations